GWSF-EuSWAP70 gene expression to enhance gray mold resistance in Arabidopsis thaliana - Zhenchi Huang; Xiaoming Li; Fenglian Cai; Lichun Li; Zhihua Wu (BMC Plant Biology)
Abstract Background Eucalyptus, a widely cultivated woody plant, is susceptible to a diverse array of pests and diseases, leading to reduced yields and economic losses. Traditional breeding methods are very time-consuming; therefore, plant genetic engineering has emerged as a promising approach for plant pathogen management. However, the genetic transformation system of eucalyptus is still in its early stages of development, while studies on transgenic eucalyptus and its disease resistance genes are limited. The SWAP70 gene has been shown to play a crucial role in the defense response of Arabidopsis thaliana and rice. In this study, the model plant A. thaliana was selected for genetic transformation. The aim was to enhance the expression of the EuSWAP70 gene derived from Eucalyptus grandis, and other disease resistance genes by utilizing an artificial GWSF promoter. Results The results showed that the EuSWAP70 gene was successfully transformed into A. thaliana, and the PCR assay confirmed the presence of the EuSWAP70 gene in transgenic Arabidopsis plants. The gray mold resistance of the EuSWAP70 transgenic Arabidopsis plants under GWSF and CaMV35S promoters was evaluated against Botrytis cinerea infection. After gray mold infection, Arabidopsis plants were ranked by leaf pore area percentage: wildtype > CaMV35S-EuSWAP70 > GWSF-EuSWAP70. The transgenic plants showed stronger gray mold resistance, and the GWSF-EuSWAP70 transgenic plants were stronger than the CaMV35S-EuSWAP70 transgenic plants.